African Religion Defined : a Systematic Study of Ancestor Worship among the Akan. - Ephirim-Donkor, Anthony (University Press of America, 2012)
The author, a traditional king and professor, studies the Akan in Ghana to demonstrate that ancestor worship is as pragmatic, systematic, theological, teleological, soteriological - with a highly trained clerical body and elders as mediators - and symbolic as any other religion in the world.